Hepatitis B virus vaccine and chronic kidney disease: the advances - Fabrizi, Fabrizio (2021)
Background: Hepatitis B is an important agent of liver disease in patients with chronic kidney disease and chronic HBV infection promotes the development of CKD in the adult general population. Patients with CKD have a suboptimal response to various vaccines, and it remains unclear how we boost the immune response of CKD patients to HB vaccine. Study aims and design: We performed a narrative review to assess the mechanisms of lower immunogenicity of HBV vaccine in CKD population; multiple approaches to improve the response rate of CKD patients to HBV vaccine have been reported. This is a very important topic for nephrologists who often serve as primary case providers for patients with CKD. Results: The recommended vaccine schedule for CKD patients including those on maintenance dialysis is based on recombinant vaccine, four doses (month 0,1,2, and 6; 40 mcg each) by intramuscular route (deltoid muscle). According to RCTs or observational studies, some recombinant vaccines with adjuvants (i.e., HBV-AS02 and HBV-AS04) look promising. HBV-AS04 showed to give better seroprotection rates and durable immune response over extended follow-ups compared with licensed HBV vaccine in CKD patients. The seroprotection rate was 95% (97/102) and 82% (202/248) in pre-dialysis and dialysis patients, respectively, one month after completing vaccine schedule with HBV-AS04. HBV-AS02 was superior to licensed vaccine in terms of seroprotection rate, 76.9% vs. 37.6%. Conclusions: We suggest adjuvanted recombinant (HBV-AS04) vaccine (0,1,2 and 3 months; 20 mcg each dose) and post vaccination testing of anti-HBs antibody after vaccination. Booster doses to patients whose anti-HBs titers fall below the seroprotection level (<10 IU/mL) during the follow-up are appropriate. The patho-physiologic mechanisms responsible for the poor immunogenicity of HBV vaccine in CKD patients are under active investigation.